Is End-Stage Ankle Arthrosis Best Managed with Total Ankle Replacement or Arthrodesis? A Systematic Review - Robert W. Jordan; Gurdip S. Chahal; Anna Chapman (Advances in Orthopedics)
Introduction. End-stage ankle osteoarthritis is a debilitating condition. Traditionally, ankle arthrodesis (AA) has been the surgical intervention of choice but the emergence of total ankle replacement (TAR) has challenged this concept. This systematic review aims to address whether TAR or AA is optimal in terms of functional outcomes. Methods. We conducted a systematic review according to PRISMA checklist using the online databases Medline and EMBASE after January 1, 2005. Participants must be skeletally mature and suffering from ankle arthrosis of any cause. The intervention had to be an uncemented TAR comprising two or three modular components. The comparative group could include any type of ankle arthrodesis, either open or arthroscopic, using any implant for fixation. The study must have reported at least one functional outcome measure. Results. Of the four studies included, two reported some significant improvement in functional outcome in favour of TAR. The complication rate was higher in the TAR group. However, the quality of studies reviewed was poor and the methodological weaknesses limited any definitive conclusions being drawn. Conclusion. The available literature is insufficient to conclude which treatment is superior. Further research is indicated and should be in the form of an adequately powered randomised controlled trial.